PENGINTEGRASIAN BUDAYA MELAYU DALAM PENGEMBANGAN PERANGKAT PEMBELAJARAN KOLOID UNTUK PENINGKATAN PENDIDIKAN KARAKTER PESERTA DIDIK - Sri Haryati; Erviyenni Erviyenni; Usman Rery; Elva Yasmi; Fauzia Rahmi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2017)
The research aims to develop devices integrated learning Malay culture in the form of RPP, LKPD and evaluation tools to improve character education learners. This type of research is the development of research (research and the development) with the procedural model. Research has been conducted in the development of chemistry teaching lab FKIP Riau University from June to November 2016. The prototype learning device generated through research is Learning Implementation Plan (RPP) consisting of 4x meeting, Activity Sheet Students (LKPD) for 4x meetings and 1 set of tools evaluation. Product prototype learning device has been evaluated by 3 validator. Data collected through questionnaires and observation techniques. The data analysis technique is a descriptive quantitative by calculating the percentage of the value of the validation. The average score ratings seventh aspect of the RPP is 95.95% with a valid category. The average score of the four aspects of the feasibility assessment LKPD is 95.95% with a valid category. The average score of all fifth aspects of the feasibility assessment evaluation tool was 94.58% with a valid category. While the percentage of learners response to LKPD is 97.36% which is at the criteria very well.